Populações de plantas e doses de nitrogênio para produção de silagem de milho - Nielsen Filho, Pedro Rodolfo (2023)
The objective was to evaluate the influence of plant populations (67, 80 and 96 thousand plants/ha) and nitrogen doses (100 and 200 kg/ha) N in top dressing for maize silage production. The experimental design used was randomized blocks with treatments in a factorial arrangement (3x2), using four replications of area in two agricultural seasons. Maize sowing was carried out in October 2021 and February 2022 through the no-tillage system, with row spacing of 45 cm. The fertilization was 80 kg of P2O5, 50 kg of N and 130 kg of K2O. The spread urea fertilization (100 or 200 Kg of N/ha) was carried between the phenological stages V4 and V8. the harvest was carried out when the plants of each plot were between Kernel dough stage and kernel dent stage. Were evaluated the initial and final stand, biometric measures of the plants, yield components, morphological components, forage productivity, nutrient export and qualitative characteristics of the silage. For that, four experimental silos of each plot were made and opened after 60 days. The silos were made in plastic bags (20 microns) with a capacity of 1 kg and stored in a without light place, and anaerobiosis was established with an Industrial Vacuum Packing Machine (model GS62OF). The off-season period, characterized by a higher incidence of the stunting complex, negatively influenced (P<0.05) the productive aspects of maize, but the silage had a lower pH, higher crude protein and neutral detergent fiber content. Plant population did not influence (P>0.05) biometric measurements, yield components and morphological components of maize plants. Forage production was higher (P<0.05) for higher plant population, which did not differ from each other. The nitrogen (N) and potassium export (K) were higher (P<0.05) for the largest population of plants compared to the others, which did not differ from each other. Phosphorus (P) export did not differ (P>0.05) between plant population. Plant population did not influence (P>0.05) the qualitative variables of maize silage. The doses did not influence (P>0.05) the productive variables and N, P and K export from the maize for silage production. The N and crude protein content was higher (P<0.05) for the silage submitted to a higher dose of nitrogen dose. The other qualitative variables of the silage were not altered (P>0.05) by the dose of N in top dressing. Increasing the maize plant population can be a viable strategy to maximize silage production.